Can spacetime superposition alleviate gravitationally induced quantum decoherence? - Changjing Zeng; Qianqian Liu; Cuihong Wen; Jieci Wang (New Journal of Physics)
As a combination of the microscopic structure of spacetime and the principle of quantum superposition, the study of spacetime superposition provides a fundamental bottom-up approach to a comprehensive understanding of relativity and quantum theory. In this paper, we study how quantum gravitational effects generated by the superposition of the black hole’s masses affect the many-body entanglement for Dirac fields. The main obstacle to performing quantum information processing tasks near a classical black hole is the inevitable entanglement degradation caused by the Unruh–Hawking thermal bath. Fortunately, here we find that the many-body quantum system near a black hole with superposing masses exhibits more entanglement compared to those in the classical black hole background. The superposition properties of spacetime are found to provide additional quantum resources for mitigating gravitationally induced quantum decoherence and improving the efficiency of quantum information tasks in curved spacetime. In addition, the greatest quantum advantage for the recovery of entanglement in the curved spacetime can be obtained by preparing an optimal initial state.